Ethical consumption, meaningful substitution and the challenges of vegetarianism advocacy. Issue 2 (11th December 2014) - Neo, Harvey
Abstract : Vegetarianism is viewed by its advocates as ethical food consumption par excellence. Yet the steady, albeit modest, growth in vegetarians worldwide is paradoxically set against an increase in global meat consumption. This study draws on the literature of ethical consumption to illuminate the practical challenges in vegetarianism advocacy. Research on ethical food consumption focuses on three main lines of inquiry, namely how is ethical food defined; under what socio‐spatial conditions do consumers choose to consume (or not consume) ethical food and what ends do consumers hope to achieve by consuming ethically. This article details the discursive framings of anti‐meat advocacy and shows how such framings fall short of presenting vegetarianism as a form of ethical food consumption. The challenges in persuading consumers to stop meat consumption (as opposed to merely reducing consumption) are well known. In this paper, I highlight a less discussed challenge, relating to the lack of 'real' substitutes for meat, in anti‐meat advocacy. Through a discussion of what I will call the problem of 'meaningful substitution', I address a comparatively under‐explored question in ethical food consumption research: what is the relative (ethical) relationship between two products? Addressing this question sheds light on our very definition of ethical product and consumption, as well as the challenges of ethical consumption advocacy. Through a series of in‐depth interviews with vegetarians (both advocates and non‐advocates) in Taipei, Taiwan, I conclude that the various moral and nature‐based framings of vegetarianism, as a form of ethical food consumption, are weakened by the lack of a meaningful substitute. More broadly, the study speaks to the practical politics and policies in the effective promotion of ethical consumption.